Tres nuevas especies en las Asclepiadaceae sudamericanas - Morillo Gilberto (Caldasia)
Three new species of South American asclepiadaceae are described within the genera blepharodon decne, ditassa R. Br. and matelea aubl. New species are blepharodon polydori morillo, ditassa macarenae morillo and matelea ampiyacuensis morillo. Se describen tres nuevas especies dentro de las Asclepiadaceae sudamericanas, correspondientes a los géneros Blepharodon Decne., Ditassa R. Br. y Matelea Aubl. Las nuevas especies son: Blepharodon polydori Morillo, Ditassa macarena e Morillo y Matelea smpiyacuensis Morillo